2017
DOI: 10.1111/ejn.13673
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pair bonding on parental behavior and dopamine activity in the nucleus accumbens in male prairie voles

Abstract: Male parental care is a vital behavior for the development as well as the physical and mental well-being of the young. However, little is known about the neurochemical regulation of male parental behavior, mainly due to the lack of appropriate animal models. In the present study, we used the socially monogamous male prairie vole (Microtus ochrogaster) to investigate the effect of pair bonding experience on paternal behavior and dopamine (DA) signaling in the nucleus accumbens (NAcc) in the brain. We compared s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 72 publications
2
25
2
Order By: Relevance
“…In parents, dopamine increases in NAc core during pup approach is consistently higher than that in nonparental animals. This result is in contrast to the previous finding showing that dopamine 26 responses to pups are similar in males with low and high parental motivation (Lei et al, 2017). This discrepancy is likely due to the low temporal resolution of microdialysis.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In parents, dopamine increases in NAc core during pup approach is consistently higher than that in nonparental animals. This result is in contrast to the previous finding showing that dopamine 26 responses to pups are similar in males with low and high parental motivation (Lei et al, 2017). This discrepancy is likely due to the low temporal resolution of microdialysis.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, nearly all studies on parental behaviors have focused on mothers probably due to the fact that mother is the main care giver. One study showed that dopamine release to pups in NAc in naïve and pair-bonded male prairie voles are quantitatively similar although pair-bonded males show enhanced paternal behavior (Lei et al, 2017). These results raise the question of whether pup-triggered dopamine release in males varies with the paternal state as is the case in females (Afonso et al, 2008; Afonso et al, 2009; Champagne et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In male prairie voles, pharmacological manipulations show that D1 receptors in NAc prevent pair-bond formation, whereas D2 receptors facilitate bonding. After bonding, D1 receptors in NAc upregulate and these receptors underlie selective aggression that is used to maintain bonds (Aragona et al, 2006; Lei et al, 2017; Resendez et al, 2016). These results raise the possibility that an increase in D1 over D2 receptors in NAc after pairing may promote pair-bond maintenance.…”
mentioning
confidence: 99%
“…These results raise the possibility that an increase in D1 over D2 receptors in NAc after pairing may promote pair-bond maintenance. It has also been proposed that an increase in D1 over D2 receptors in NAc may underlie rewarding effects related to paternal bonds with pups in mandarin voles (Fang & Wang, 2017; Lei et al, 2017). These findings suggest that the ratio of D1 over D2 in NAc may underlie important behaviors related to bond maintenance.…”
mentioning
confidence: 99%
“…To investigate whether the separation of a social pair causes any side effect or stress‐induced brain activation, a supplementary experiment was carried out. Social pairs ( n = 10) without a nesting opportunity were kept together for 2 weeks to form pair bonds (Aragona et al, ; Lei, Liu, Smith, Lonstein, & Wang, ). In the separated group, social pairs were isolated from each other for 16 hr ( n = 5), while social pairs stayed together with their mate in the paired group ( n = 5).…”
Section: Methodsmentioning
confidence: 99%